Research for development in agricultural and tree biodiversity - Bioversity International (2016)
A short booklet that describes how and why Bioversity International carries out research for development in agricultural and tree biodiversity. The booklet gives information about why agricultural and tree biodiversity matters for sustainable development, our strategic initiatives, where we work and our areas of scientific expertise. Find out more on www.bioversityinternational.org